Kewenangan Notaris Dalam Pendirian Perseroan Perorangan Berdasarkan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Fajar Rafiqi Reynaldi (Officium Notarium, 2021)
This study examines the authority of a notary in the establishment of an individual company based on Law Number 11 of 2020 on Job Creation. The problems formulated are first, how is the authority of a notary in the establishment of an individual company based on the amendment to Law Number 11 of 2020 on Job Creation, and second, what is the responsibility of a notary in the change in the establishment of an individual company based on Law Number 11 of 2020 concerning Job Creation. This type of research is normative with a statutory approach and a conceptual approach. The method used is literature study, and the data is processed non-statistically and analyzed descriptively-qualitatively. The results of the study conclude firstly, that a notary has no authority in the process of establishing a private company as regulated in the Job Creation Law and its derivative regulations Government Regulation Number 8 of 2021, the authorized capital of the company and the registration of the establishment, amendment, and dissolution of companies that meet the criteria for micro businesses. and Small. Second, the establishment of an individual company that meets the requirements for micro and small businesses is the responsibility of the person concerned (founder/shareholder), hence it is the responsibility of the person concerned, not the responsibility of a notaryKey Word: Individual Company, Omnibus Law, Power of NotaryAbstrakPenelitian ini meneliti tentang kewenangan notaris dalam pendirian Perseroan Perorangan berdasarkan Undang - Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja. Masalah yang dirumuskan, pertama, bagaimana kewenangan notaris dalam pendirian Perseroan Perorangan berdasarkan perubahan Undang - Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja, dan kedua, bagaimana tanggung jawab notaris dalam Perubahan pendirian Perseroan Perorangan berdasarkan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja. Jenis penelitian ini adalah normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Metode yang digunakan adalah dengan studi kepustakaan, dan data diolah secara non-statistik dan dianalisis secara deskriptif-kualitatif. Hasil penelitian menyimpulkan  pertama, bahwa notaris tidak memiliki kewenangan dalam proses pendirian Perseroan Perorangan seperti yang telah diatur dalam UU Cipta kerja dan peraturan turunannya Peraturan Pemerintah Nomor 8 Tahun 2021 tentang Modal Dasar Perseroan Serta Pendaftaran Pendirian, Perubahan, dan Pembubaran Perseroan yang Memenuhi Kriteria untuk Usaha Mikro dan Kecil. Kedua, pendirian Perseroan Perorangan yang memenuhi syarat Usaha Mikro dan Kecil tersebut merupakan tanggungjawab yang bersangkutan (pendiri/pemegang saham), sehingga menjadi tanggung jawab yang bersangkutan, bukan menjadi tanggungjawab notarisKata Kunci: Kewenangan Notaris, Perseron Perorangan, UU Cita kerja